2019
DOI: 10.1002/jcb.29195
|View full text |Cite
|
Sign up to set email alerts
|

The heat shock protein 70 inhibitor VER155008 suppresses the expression of HSP27, HOP and HSP90β and the androgen receptor, induces apoptosis, and attenuates prostate cancer cell growth

Abstract: Heat shock proteins (HSPs) are molecular chaperones that play a pivotal role in correct folding, stabilization and intracellular transport of many client proteins including those involved in oncogenesis. HSP70, which is frequently overexpressed in prostate cancer (PCa), has been shown to critically contribute to tumor cell survival, and might therefore represent a potential therapeutic target. We treated both the androgen receptor (AR)‐positive LNCaP and the AR‐negative PC‐3 cell lines with the pharmacologic H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…5a, c, e-f). Previous works had reported that these two HSP proteins are involved in the progression of multiple types of cancers [33][34][35]. HSP70 and HSP27 may also play a role in the tumorigenesis of ESCC following the overactivation of TRPV2.…”
Section: Overactivation Of Trpv2 Activates Hsp and Pi3k/akt/mtor Signmentioning
confidence: 99%
“…5a, c, e-f). Previous works had reported that these two HSP proteins are involved in the progression of multiple types of cancers [33][34][35]. HSP70 and HSP27 may also play a role in the tumorigenesis of ESCC following the overactivation of TRPV2.…”
Section: Overactivation Of Trpv2 Activates Hsp and Pi3k/akt/mtor Signmentioning
confidence: 99%
“…negative chaperonotherapy. In this regard, current research aims at finding and standardizing compounds and delivery means targeting as specifically as possible the pathogenic chaperone [82][83][84][85][86]. If the chaperonopathy is by defect, positive chaperonotherapy is indicated, consisting in chaperone gene or protein replacement, or the use of manufactured chaperoning structures [87][88][89]; or chaperone-protein functional boosting with chemical compounds, namely chemical chaperones similar to those utilized for restoring enzymatic activity in genetic enzymopathies [82,[90][91][92][93].…”
Section: Conclusion and Perspectives For The Futurementioning
confidence: 99%
“…On the other hand, a marked and rapid overexpression of most HSPs in response to cellular damage is found, with cancer cells having been found to over-stimulate the synthesis of heat shock proteins [15]. This may be of fundamental importance in the pathogenesis and progression of cancerthe significant role of heat shock proteins as a therapeutic target in cancer has been demonstrated [16,17] but, on the other hand, they are also associated with drug resistance in cancer [18].…”
Section: Introductionmentioning
confidence: 99%